2012
DOI: 10.17660/actahortic.2012.944.17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Glucosinolate Content Within Brassica Rapa Vegetables

Abstract: Glucosinolates (GSs) were analyzed in 56 accessions of Brassica rapa grown in the greenhouse. Eight different glucosinolates were identified in the Brassica rapa group. They are the aliphatic glucosinolates progoitrin (PRO), gluconapin (NAP), glucobrassicanapin (GBN), the indolyl glucosinolates 4-hydroxyglucobrassicin (4OH), glucobrassicin (GBC), 4-methoxyglucobrassicin (4ME), neoglucobrassicin (NEO) and the aromatic glucosinolate gluconasturtiin (NAS). Gluconapin, glucobrassicanapin, progoitrin and gluconastu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(56 reference statements)
0
6
1
Order By: Relevance
“…However, the least detected GSL was GBC according to He and co-workers [ 30 ], contrasting with the Sinalbin (SNB) compound that is observed in our current study [ 31 ]. Clear variations in GSL content and individual GSL profiles exists among Brassica vegetables [ 30 , 32 ]. For example, leaf mustard ( B. juncea ), turnips ( B. rapa var.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…However, the least detected GSL was GBC according to He and co-workers [ 30 ], contrasting with the Sinalbin (SNB) compound that is observed in our current study [ 31 ]. Clear variations in GSL content and individual GSL profiles exists among Brassica vegetables [ 30 , 32 ]. For example, leaf mustard ( B. juncea ), turnips ( B. rapa var.…”
Section: Resultscontrasting
confidence: 63%
“…Previous studies on GSLs from various B. rapa vegetables revealed that choi sum has high GNA content compared to other Brassica vegetables [ 12 , 30 ]. However, the least detected GSL was GBC according to He and co-workers [ 30 ], contrasting with the Sinalbin (SNB) compound that is observed in our current study [ 31 ]. Clear variations in GSL content and individual GSL profiles exists among Brassica vegetables [ 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, glucobrassicin, an indolic GSL was detected at an average of 333.30 µmol·kg −1 DW, accounting for 3.62% of the total GSLs ( Figure 1 ). Several studies have been made on the GSL content of plants, especially Brassica vegetables [ 12 , 18 , 25 , 26 , 27 ]. Earlier studies on the GSLs from various rapa vegetables indicated that choy sum possessed specifically high levels of GNA among the GSLs compared to other vegetables of Brassica [ 18 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been made on the GSL content of plants, especially Brassica vegetables [ 12 , 18 , 25 , 26 , 27 ]. Earlier studies on the GSLs from various rapa vegetables indicated that choy sum possessed specifically high levels of GNA among the GSLs compared to other vegetables of Brassica [ 18 , 25 ]. However, the least detected GSL was GBC in the case of He et al, 2003, against SNB observed in the current study [ 18 ].…”
Section: Resultsmentioning
confidence: 99%